"Between Ownership and the Highway": Property, Persons, and Freeways in Karen Tei Yamashita's Tropic of Orange. (25th October 2021) - BALACHANDRAN ORIHUELA, SHARADA
Abstract : "'Between Ownership and the Highway': Property, Persons, and Freeways in Karen Tei Yamashita's Tropic of Orange" examines the place of the Los Angeles freeway system in the creation and maintenance of the egalitarian communities imagined in the novel. As I show, the freeway serves as an instrument for the economic growth, securitization, and increased powers of the state. Thus, in misusing the freeway, the migrants, narcotraffickers, and homeless stage a resistance to the freeway as metonym for modernity, efficiency, progress, and economic advancement. However, given that the threat posed by the ascendance of the homeless in particular must be understood through discourses regarding the public threat of unlawful migration and narcotrafficking, the homeless represent a population critical both to unmaking the extant state and replacing it with a more equitable society. I reanimate discussions of the novel by proposing that rather than examine transnational migration, and the mutations of time and space figured so prominently in the text as the novel's primary mode of critique, scholars instead turn their attention to the homeless encampment atop the LA freeway system as the boldest insight into how a new political system might be conceived.